Temperature During Convective Drying of Thin Flat Wet Materials - A. I. Ol’shanskii; A. A. Kotow; S. M. Kuzmenkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
. The basic laws of the kinetics of drying thin flat materials during the period of drop in the drying speed are outlined. A method for calculating the average integral temperature of wet material on the basis of the relative temperature coefficient of drying is presented. Experimental data are processed based on the relative drying rate in the drying processes of ceramics, asbestos, and woolen fabric. A formula for calculating the average temperature is proposed. The solution of the differential equation of thermal conductivity for a wet plate during the drying process (namely during the period of drop in the drying speed) under boundary conditions taking into account the conditions of drying is given. The calculation of the heat transfer coefficient is given, too. Based on the study of various sources and processing of experimental results, formulas for calculating the thermal conductivity coefficient of wet materials have been presented. The analytical solution of the problem confirmed that during convective drying in low-intensity processes of the second drying period, the temperature change with a decrease in moisture content turns from an exponential dependence smoothly into a linear one, which is completely consistent with the experiment.  A comparison of the temperature calculation by the experimental formula with the results of analytical solutions has been presented. A sufficiently reliable coincidence of experimental and calculated analytical values of temperature for the period of drop in speed drying of ceramics, asbestos, and fabric is obtained.